Severe sacroiliitis in the occupationaly active man with chronic Chlamydia trachomatis infection - Cieślak, Dorota; Leszczyński, Piotr; K. Łącki, Jan (Reumatologia/Rheumatology, 2005)
The case of 29 years old working man suffering from severe inflammation of sacroiliac joints accompanied by a strong pain caused by prolonged, not treated infection with Chlamydia trachomatis was described. Computed tomography and x-ray of sacroiliac joints confirmed this inflammation. DNA of Chlamydia trachomatis was found in a swab of urethra. After long- term therapy with salazopiryne, doxycycline and non-steroid antiinflammatory drugs a great improvement of patient’s clinical condition was reached.